Wireframe Aplikasi Layanan Sewa Kamar Kost Puri Adiwijoyo Berbasis Website - Sunardi, S; Ibrahim, A. F.; Listiyono, Hersatoto (LPPM STIKOM Tunas Bangsa, 2024)
The demand for affordable yet comfortable boarding houses for students and employees has increased rapidly. However, the perception that a good boarding house is one that is affordable with luxurious facilities presents a challenge. Likewise, for boarding house owners, even though they have listed their boarding house on Google Maps to reach potential tenants, it would be better to include detailed boarding house information. Therefore, the development of this web-based application aims to provide easy access to information for boarding house tenants.The application development method begins with conducting research through direct interviews with owners to identify the necessary features. This application design adapts a dynamic user interface to provide convenience across various devices. The aim of this development is to create a website application that can facilitate room rental activities at Kost Puri Adiwijoyo, which is expected to overcome several system constraints, such as booking and recording tenant information that is not yet managed in real-time. The result of this research is a website application that can be accessed through any device. Through this application, tenants can view detailed boarding house information and make online bookings, while owners can add or modify boarding house information and view tenant information in an integrated manner. The final result is that the development of the website application can be an effective solution in providing information and rental services for boarding house rooms. This application offers benefits by providing easily accessible detailed boarding house information, accessible through devices via a browser.